Experimental investigation of pile-supported/floating breakwaters integrated with oscillating-water-column converters - He, Fang (2013)
Nowadays, more than half of the world population live in coastal regions, and coastal areas are vital with many economic benefits. Breakwaters are commonly used to protect harbors and coasts from wave attack. Traditional bottom-sitting breakwaters can effectively fulfill the demands of harbor protection in places where water is relatively shallow. However, the heavy traffic and large ship tonnage due to rapidly-developed international trade and maritime transportation are demanding much deeper water depth in harbors. As a result, new harbors are extending towards the ocean and traditional bottom-sitting breakwaters are no longer suitable economically. There is a need for new types of breakwaters that can effectively and economically be deployed in places where water is deep or bottom foundation is weak. Since wave energy mainly concentrates near the water surface, and exponentially decreases with increasing distance from the water surface, pile-supported breakwaters and floating breakwaters may be good alternatives to traditional breakwaters. Most of the existing designs make use of vortex shedding, turbulence and/or wave breaking to enhance dissipation of wave energy. However, wave energy can also be used for electricity generation, and integration of a wave energy converter into a breakwater potentially can be a promising technology for waste-to-energy. The structural simplicity, operating principle and their adaptability make oscillating-water-column types of converters very suitable for being integrated into breakwaters. The civil construction dominates the cost of most coastal structures, and integration of an oscillating-water-column converter into breakwater make it possible to share the construction costs between power generation and harbor protection. In this thesis, four novel designs, which are multi-functional and low in construction costs, were investigated experimentally. All these designs were originated with the idea of integrating a wave energy converter into a pile-supported/floating breakwater: (1) Hydrodynamic performance of a pile-supported oscillating-water-column structure as a breakwater was experimentally investigated. The wave-transmission performance of the pile-supported OWC structure was remarkable compared with other types of pile-supported breakwaters, and the pile-supported OWC structure also had the potential for wave energy utilization. (2) Hydrodynamic performance of two configurations of a pneumatic chamber in front of a vertical wall was experimentally investigated to examine their performance in reducing wave reflection. For a pneumatic chamber without a top opening, large energy dissipation occurred in a narrow range of frequency when the water column within the gap responded to incoming waves resonantly, resulting in very small reflection coefficients. For a pneumatic chamber with a small top opening, energy dissipation came mainly from the air flow through the small top opening and the vortex shedding at the tips of the pneumatic chamber walls; both small reflection coefficients and large energy extraction efficiencies were achieved when the rear wall of the pneumatic chamber is part of the vertical wall. (3) Hydrodynamic performance of a floating breakwater with and without pneumatic chambers was experimentally investigated. The installation of pneumatic chambers to both sides of a floating breakwater was more effective for wave transmission reduction, and also had the potential for simultaneous wave energy conversion for electricity generation. However, given the same geometry of the two pneumatic chambers, the rear chamber did not function as efficiently as the front chamber in terms of extracting wave energy. (4) Hydrodynamic performance of a floating breakwater with asymmetric pneumatic chambers (a narrower chamber on the seaside and a wider chamber on the leeside) was experimentally investigated. The breakwater with asymmetric chambers performed as good as that with symmetric chambers in terms of wave transmission and motion responses. Meanwhile, an asymmetric configuration made it possible to increase the amplitude of the oscillating air-pressures inside both chambers without sacrificing the breakwater function. The experimental investigation in this thesis demonstrated that integrating an oscillating-water-column converter into a pile-supported/floating breakwater could achieve both wave transmission reduction and wave energy extraction.